Nilai Budaya Pedagang Pasar Triwindu dalam Peningkatan Kesejahteraan Sosial - Fatwa Nurul Hakim (ARISTO, 2017)
The market has functioned as a safety net and employment provider for some communities. Traditional market as a symbol of people's prosperity in every region. This research is conducted to know the culture in Triwindu Market as one of antique market in Surakarta City. Cultural value is expected in accordance with the local wisdom of the city of Surakarta as a city that preserves the culture and cultural values as a crutch to improve the welfare of merchants this research using descriptive qualitative method with purposive sampling and unit analysis of traders antiques merchants motor parts, Heirloom traders, scales traders. Data collection using in-depth interviews. The result of the Culture which is the philosophy that developed in the merchant community and still used as one of the trading principles is "kintir ora keli" which means although following the current trade flows or developing trend but not to lose its trade identity. There is also "jeneng first new jenang" which means to be successful in trading must find a good name first in the eyes of buyers by providing the best service and quality assurance commodities, new customers will get a lot of fortune.